Central Retinal Thickness and Visual Acuity Outcomes After Vitrectomy for Epiretinal Membrane With and Without Internal Limiting Membrane Peel. (March 2022) - Burckhard, Braden A.; Mathews, Nathan R.; Altaweel, Michael M.; Chang, Jonathan S.; Ip, Michael S.; Gottlieb, Justin L.
Purpose: This work compares best-corrected visual acuity (BCVA) and central retinal thickness (CRT) outcome measures following pars plana vitrectomy (PPV) with and without internal limiting membrane (ILM) peel for epiretinal membrane (ERM). Methods: A retrospective cohort study was conducted of 114 eyes of 114 patients with visually significant ERM undergoing PPV with membrane peel (PPV/MP) at a single institution. CRT measurements were collected from Heidelberg and Zeiss spectral-domain optical coherence tomography imaging units. Results compared preoperative and postoperative CRT and BCVA among patients with at least 60 days of follow-up. Results: A total of 114 eyes with ERM met the inclusion criteria. Eighty-one eyes (71%) underwent PPV/MP with ILM peel and 33 eyes (29%) underwent PPV/MP without ILM peel. There was no statistically significant difference between preoperative CRT between the 2 study groups ( P = .95). The mean follow-up time of eyes undergoing PPV/MP without ILM peel and with ILM peel was 391 days and 319 days, respectively. There was no statistical difference in the mean reduction of CRT between the 2 groups ( P = .470). Both groups had improvement of BCVA following surgery and there was no statistical difference in final logMAR visual acuity when comparing the 2 groups ( P = .738). Conclusions: There was an overall improvement of CRT and BCVA among patients undergoing PPV/MP for ERM with or without ILM peel. There was no statistically significant difference in the final BCVA or CRT between the 2 groups.